Effects of Workplace Gossip on Employee Mental Health: A Moderated Mediation Model of Psychological Capital and Developmental Job Experience - Cheng, Sheng; Kuo, Chien-Chih; Chen, Huai-Chieh; Lin, Mei-Chi; Kuo, Vincent (Frontiers in Public Health, 2022)
Research has demonstrated the effects of workplace gossip on employees' work attitudes and behaviors. However, little emphasis has been placed on the psychological influence of workplace gossip on employees. The present study investigated the relationships among workplace gossip, psychological capital, and individual mental health. Data were collected in three waves from 222 full-time employees of a Taiwanese tourism company to explore the effect of workplace gossip on employees' mental health. The results suggested that workplace gossip was associated with employees' mental health through psychological capital. Moreover, developmental job experience plays a moderator role in the relationships among workplace gossip, psychological capital, and mental health. A moderated mediation model was also proposed in this study.